Mencari Solusi Manajemen Dalam Pemenuhan Target Penerimaan Pajak Dan Retribusi Parkir Di Kota Medan - Yuswar Effendy (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
The application of the concept of decentralization and regional autonomy in Indonesia especially in Medan City is still yet to show maximum results as expected, especially regarding for potential revenue.  One of these revenues to the local government that the potential is about parking.  Still found some flaws in the application of its management, including the fulfillment of tax revenue target and parking fees in the city of Medan. With the fulfillment of tax revenue target and parking fees, the city of Medan will be able to increase the independence of the region through increased income tax revenue region.  Tax effort is to increase the local tax measured by the ration between the acual source of revenue  to a source of potential revenue.  It takes qualified human resources and management oversight that maximum parking tax in Medan can contribute the maximum so as to meet the target of tax revenue and levies to support the budget.